Interim Information in Long Term Contracts - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper studies the effectiveness of interim information in reducing inefficiencies in long term relationships. If the interim information is verifiable, it resolves all problems of asymmetric information. Under nonverifiability, the information alleviates the contracting problem only partially and its optimal use depends on the signal's accuracy and timing. Precise and early signals enable the principal to extract all rents and adjust allocations closer to the first best. Imprecise or late signals affect only future allocations and leaves the agent with a rent. Due to a failure of the revelation principle, the optimal contract under non-verifiability is derived by employing the theory of communication equilibrium.
urn:nbn:de:bvb:19-epub-13508-1
Keywords: 330